Literature Review: Konsep Dasar dan Perkembangan Teori Manajemen Pengetahuan - Firdaus, Ahmad (Universitas Batanghari Jambi, 2024)
The aim of this research is to look at the basic concepts and theoretical developments related to knowledge management. This research also discusses the design and approaches to knowledge management, as well as the stages of knowledge management which are explained by several researchers from various perspectives. The analytical method used is qualitative with bibliometric analysis of literature, theoretical basis analysis, and reviewing the main concepts of knowledge management, proving and analyzing the knowledge management approach